PENGEMBANGAN LKS BERBASIS PROBLEM SOLVING PADA MATERI STATISTIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS XI: (Uji Coba di SMAN 12 Banda Aceh) - Siska Yulianti Maulia; Fitriati; Rita Novita (Jurnal Numeracy, 2017)
The purpose of this research is (1) generates Student worksheet (LKS) based problem solving on statistical material for high school students based on the model of developing Plomp, and (2) know the quality is LKS as seen from the aspect of kevalidan, effectiveness, and practicality is LKS on the material Statistics that correspond to the problem solving approach to high school students. This research is research development that consists of 3 stages, namely the stage of Early Investigas, stage Design, phase Realization/construction, the stage of the test, evaluation and Revision and stages of implementation. Activities at this stage of the analysis in the form of condition of the students analysis, analysis of the condition of the school, and the analysis of competence. Stage of the test, evaluation and Revision contains a limited trial activity is LKS in the Statistical material learning in class XI IPA 2, SMAN 12 Banda Aceh. The resulting research is LKS as bersimateri stats with problem-solving approach (problem solving) for high school students. The resulting quality is LKS as follows: (1) is LKS as valid Criteria with an average tally score assessment by experts of 4.65. (2) is LKS as developed for practical use in learning. This is apparent from an average score of 95% of teacher assessment. (3) is LKS as developed effective use in learning. It can be seen from the score of the average value of test results of study 4,1. Abstrak Tujuan penelitian ini adalah (1) menghasilkan LKS berbasis problem solving pada materi statistika untuk siswa SMA berdasarkan model pengembangan Plomp, dan (2) mengetahui kualitas LKS dilihat dari aspek kevalidan, keefektifan,dan kepraktisan LKS pada materi Statistika yang sesuai dengan pendekatan problem solving untuk siswa SMA. Penelitian ini merupakan penelitian pengembangan yang terdiri dari 3 tahap yaitu Tahap Investigas Awal (Preliminary Investigation), Tahap Perancangan (Design), Tahap Realisasi/Konstruksi (Realization/Construction), Tahap Tes, Evaluasi dan Revisi (Test, Evaluation and Revision) dan Tahap Implementasi (implementation). Kegiatan pada tahap analisis berupa analisis kondisisiswa, analisis kondisi sekolah, dan analisis kompetensi. Tahap Tes, Evaluasi dan Revisi berisi kegiatan uji coba terbatas LKS dalam pembelajaran materi Statistika di kelas XI IPA 2, SMAN 12 Banda Aceh. LKS yang dihasilkan penelitian ini bersimateri statistik dengan pendekatan pemecahan masalah (problem solving) untuk siswa SMA. Kualitas LKS yang dihasilkan sebagai berikut: (1) Kriteria LKS valid dengan rata-rata perolehan skor penilaian oleh ahli sebesar 4,65.(2) LKS yang dikembangkan praktis digunakan dalam pembelajaran. Hal ini terlihat dari rata-rata skor penilaian guru sebesar 95%.(3) LKS yang dikembangkan efektif digunakan dalam pembelajaran. Hal ini dapat dilihat dari skor rata-rata nilai tes hasil belajar sebesar 4,1. Kata kunci: LKS Berbasis Problem Solving, Problem Soving, Penelitian Pengembangan